Steroid hormones regulate sperm–oviduct interactions in the bovine - Lamy, Julie; Corbin, Emilie; Blache, Marie-Claire; Garanina, Anastasiia S; Uzbekov, Rustem; Mermillod, Pascal; Saint-Dizier, Marie (Reproduction (Cambridge, England), 2017)
After insemination in the cow, a sperm reservoir is formed within the oviducts, allowing the storage and then progressive release of spermatozoa toward the ovulated oocyte. In order to investigate the hormonal regulation of these events in vitro, the ovarian steroids 17β-estradiol (E2) and progesterone (P4) were added at various concentrations to monolayers of bovine oviduct epithelial cells (BOEC) before or during co-incubation with spermatozoa. Main findings demonstrate that (1) a 18-h pretreatment of BOEC with 100 pg/mL and 100 ng/mL of E2 decreased by 25% the ability of BOEC to bind spermatozoa after 10 min, and for the highest dose of E2, 60 min of co-incubation; (2) P4 at concentrations of 10, 100 and 1000 ng/mL induced the release within 60 min of 32–47% of bound spermatozoa from BOEC; this sperm-releasing effect was maintained after a 18-h pretreatment of BOEC with 100 pg/mL of E2; (3) E2 in concentrations above 100 pg/mL inhibited the releasing effect of P4 on bound sperm in a dose-dependent manner; (4) spermatozoa bound to BOEC, then released from BOEC by the action of P4-induced higher cleavage and blastocyst rates after in vitro fertilization than the control group. These results support the hypothesis that the dynamic changes in steroid hormones around the time of ovulation regulate the formation of the sperm reservoir and the timed delivery of capacitated spermatozoa to the site of fertilization.